Reading MUI Fatwa No. 83 of 2023 on The Ruling of Supporting The Palestina: Maslahat Perspective - Basya, Nabilah Tsuroya (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
Fatwas as a central instrument in the Islamic legal system, are often regarded as the ultimate guide for Muslims in facing the challenges of the times. However, in a complex modern era, it is important to see fatwas not only as a set of legal regulations, but also as a reflection of the values of maslahat or public interest. This research aims to read the fatwa of the Indonesian Ulema Council (MUI) no. 83 of 2023 on the Law of Supporting the Palestinian Struggle through the lens of maslahat. Through this approach, this research aims to understand how these fatwas can contribute to the welfare of the people (maslahat). By utilizing literature analysis, this research also aims to investigate the conception of maslahat in the context of fatwas. This research is a literatureresearch by using various literature sources as sources of existing research data. This research is conducted based on literature data related to the subject matter discussed with the concept of maslahat regarding reading fatwa No. 83 of 2023 concerning the Law of Support for the Palestinian Struggle with a maslahat perspective. Data sources are obtained from literature that discusses fatwas and maslahat such as articles, news, social media, and other written materials. Fatwa sebagai instrumen sentral dalam sistem hukum Islam, sering dianggap sebagai panduan utama bagi umat Islam dalam menghadapi tantangan zaman. Namun, dalam era modern yang kompleks, penting untuk melihat fatwa bukan hanya sebagai serangkaian peraturan legal, melainkan juga sebagai refleksi dari nilai-nilai maslahat atau kepentingan umum. Penelitian ini bertujuan membaca fatwa Majelis Ulama Indonesia (MUI) no. 83 Tahun 2023 tentang Hukum Dukungan terhadap Perjuangan Palestina dengan kacamata maslahat. Melalui pendekatan ini, penelitian ini bertujuan untuk memahami bagaimana fatwa-fawa tersebut dapat memberikan kontribusi pada kesejahteraan umat (maslahat). Dengan memanfaatkan analisis literatur penelitian ini juga bertujuan untuk menyelidiki konsepsi maslahat dalam konteks fatwa. Penelitian ini merupakan penelitian kepustakaan dengan menggunakan berbagai sumber literatur sebagai sumber data penelitian yang telah ada. Penelitian ini merupakan dilakukan berdasarkan data kepustakaan yang berkaitan dengan pokok bahasan yang dibahas dengan konsep maslahat mengenai membaca fatwa Nomor 83 Tahun 2023 tentang Hukum Dukungan terhadap Perjuangan Palestina dengan kacamata maslahat. Sumber data diperoleh dari literatur-literatur yang membahas tentang fatwa dan maslahat seperti artikel, berita, sosial media, dan bahan tertulis lainnya.